The Role and Duty in Moral Problems of Pastoral Councils of Sriracha Deanery, Chanthaburi Diocese. - Maha, Worawut; Chumsriphan, Rev.Dr.Surachai; Chinnawong, Rev.Dr.Apichit; Prasutsaengchan, Asst.Prof.Dr.Laddawan (Saengtham College Journal, 2020)
The research is qualitative with its purposes as following 1) to investigate the role and duty in dealing with the moral problems of the pastoral councils within the ecclesiastic deanery of Sriracha, Chantaburi Diocese and 2) to figure out the methodology for the development of its role and duty for the further implementation. The information are collected through fourteen members of the pastoral councils selected particularly, two from each parish pastoral council, one responsible for social aspect and another for educational aspect. The means used were quasi-structural interviews and 2) the documentation of the group discussion of a group of eleven experts. The statistics used to analyze the data are frequency and percentage. Analysis of the data was obtained by the interview and the discussion is content-relating analysis. The results are 1. The parish pastoral council realizes and acknowledges its role and duty towards the actual moral problems known through personal notification, conversation with the people and social media. These moral problems get worse gradually and cause the negative effects to the community and society. Some of the problems are perceived as distant; others are close and require a closer surveillance such as violence, drug addiction and self-indulgence in all-vices (abaiyamuk); natural and cultural deterioration; human trafficking or unlawful business. The parish council has its role and duty to prevent and find a way out of these problems in the Christian community including provision of integrating the moral values into the community, especially to its younger generation. 2. The directions of implementation are as follow : 2.1 The parish pastoral council must regard highly its proper position and duty towards the moral problems in the Christian community. 2.2 The pastoral council must acknowledge and recognize the moral problems, by which it tries to comprehend the cause, and then evaluate the factual situation and the eventual effects; with all of these processes the council can construct a plan to prevent the moral problems and to integrate moral values into the community. 2.3 The pastoral councils must work together to make these plans. 2.4 The pastoral councils must follow the plan through network of government or private cooperations. 2.5 The plans must be followed-up with evaluation and continual sustenance both officially, through discussions in the plenary agenda of the council’s meeting; and unofficially, through visitation and intervention. 2.6 The result of the work in progress must be developed into the better strategy which would be more effective in dealing with the moral problems and in integration of moral values into the community.